Works About the Formative Assessment of Biological Subjects and Its Implementation Methods - Ziaullah Ahmadzai; Khwaja Mohammad Charkhi; Abdul Zahir Mohsin (Randwick International of Education and Linguistics Science Journal, 2022)
This article hands us information about formative assessment in biological class's subjects. So, we conducted a research about it. Formative assessment is not a sort of the assessment in which students are given the score or they are graded by, but it used to engage the students in high qualitative and elite learning. It actually happens while the lecturer is teaching. So, it doesn't have a specific time. The Formative assessment can easily be applied through four popular methods: 1- The method of asking questions, 2- The method of giving feedback on students' work, 3- self-rectification, 4- Using the pre-test for learning. The teachers can carry the formative assessment through these methods in biological subject’s class in order to be get the accurate learning in the students.